2022
DOI: 10.1088/1361-6463/ac4f91
|View full text |Cite
|
Sign up to set email alerts
|

Flexible force sensitive frequency reconfigurable antenna base on stretchable conductive fabric

Abstract: With the development of wireless technology and flexible electronics, flexible frequency reconfigurable antennas have been directly used as sensors to detect mechanical signals. As an important frequency reconfigurable antenna, microstrip antenna has been widely studied in the field of flexible and flexible electronics in recent years. However, the stretchability of microstrip antennas usually comes at the cost of reducing the conductivity of the radiated conductor. Here, we report a flexible force sensitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Overall, comparing Figs. (16)(17)(18)(19)(20)(21) it can be concluded that when concave deformations are considered the spherical deformation is better correlated with the cylindrical bending along antenna length when the impact on the resonant frequency is considered but better correlated to the cylindrical bending along the width of antenna when fractional bandwidth is considered. For the case of convex deformations, the spherical deformation is better correlated to the cylindrical bending along the width of antenna when the impact on both the resonant frequency and the bandwidth is considered.…”
Section: Comparison With the Cylindrical Deformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, comparing Figs. (16)(17)(18)(19)(20)(21) it can be concluded that when concave deformations are considered the spherical deformation is better correlated with the cylindrical bending along antenna length when the impact on the resonant frequency is considered but better correlated to the cylindrical bending along the width of antenna when fractional bandwidth is considered. For the case of convex deformations, the spherical deformation is better correlated to the cylindrical bending along the width of antenna when the impact on both the resonant frequency and the bandwidth is considered.…”
Section: Comparison With the Cylindrical Deformationsmentioning
confidence: 99%
“…Integration of antennas into clothing means that the antennas will be affected by the dynamics of the human body that can cause a variety of deformations [15][16][17][18][19] which in turn can degrade the overall system's performance and present a challenging design task for wearable antenna design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the existing reports, it is known that the bending angle of antennas has a significant impact on their working frequency and pattern [ 22 ]. Hu et al [ 23 ] prepared the reconfigurable antenna by layering, which laid the foundation for the feasibility of the research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the MMAs that have been designed so far have a fixed operating bandwidth, which means that they can only work in a limited area. For example, absorbers designed in the X-band (8-12 GHz) and Kuband (12-18 GHz) can be used as absorbing microwave radars [29][30][31] to reduce the RCS of a target and reduce the chance of detection by the enemy, while millimeter wave radars operating in the Ka (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) band are also being used on the battlefield as detection technology continues to develop [32]. Designed in the C-band (4-8 GHz) or Ku-band MMAs can be used in satellite communications [33][34][35], but with the increasing depletion of satellite orbit resources in C and Ku-band, satellite communications in Ka-band have become a latecomer [36].…”
Section: Introductionmentioning
confidence: 99%